The Role of the Community in Improving the Quality of Slums in Pematang Siantar: The Case of the Bantan Area - Edi Saputra; Abdi Sugiarto (Journal of Information Technology, computer science and Electrical Engineering, 2024)
This study aims to examine the Role of the Community in Improving the Quality of Slums in Pematang Siantar: The Case of the Bantan Area. This research uses a qualitative approach. The type of research used is a case study. The Bantan area in Pematang Siantar is used as a study location to obtain empirical data on the role of the community in the process of improving the quality of slums. Data analysis is carried out with a thematic analysis approach. In this study, data from interviews, observations, and documents were compared to ensure the consistency and validity of the information obtained. The results of the research of the community in the Bantan area, Pematang Siantar, play a very important role in efforts to improve the quality of slums. Active involvement of residents in every stage, from planning to implementation and maintenance of program results, is the key to the success of settlement improvement. Several obstacles faced by the community in participating, such as limited knowledge, economic limitations, and unequal access to information, are the main obstacles in achieving maximum results. Strategies such as community counseling and education, mutual cooperation revitalization, strengthening the citizens' economy, and simplifying access to bureaucracy and information, have been proven to encourage community participation more effectively. Good collaboration between the government, local organizations, and the community can accelerate the process of improving the quality of slums in the Bantan area.